PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN METODE WARD AND PEPPARD PADA RSUD HUSADA PRIMA - Safitri, Eristya Maya; Ramdhani, Moch. Abdillah Emha; Robawa, Rizki Setyo Putro; Putra, RM Mohd. Pujangga Kharisma (Universitas Lampung, 2025)
As an innovative and trusted healthcare provider in Surabaya. Information systems (IS) and information technology (IT) play an important role in supporting operations and achieving strategic goals of organizations, including hospitals. RSUD Husada Prima faces challenges in managing patient data, electronic medical records, and financial reports. This study uses the Ward and Peppard method to design strategic IS/IT planning that supports the hospital's vision and mission. The analysis was carried out using tools such as SWOT, PEST, Value Chain, Porter's Five Forces, Critical Success Factors, and McFarlan Strategic Grid. The result is an application portfolio that includes strategic, operational, supporting, and high-potential applications. Technology recommendations include integration of the Hospital Management Information System (SIMRS), telemedicine services, big data, and artificial intelligence (AI). This implementation aims to improve operational efficiency, service quality, and hospital competitiveness. This study provides a strategic roadmap for RSUD Husada Prima to adopt modern technology and strengthen its position.